Snap diagnosis of fulminant type 1 diabetes by the normalized glucose/HbA1c ratio - Jun-Ichiro Mori; Takahiro Miyakoshi; Hanae Yuzuriha; Teruki Kondo; Eita Nishimori; Motoji Naka; Ai Sato; Mitsuhisa Komatsu; Koh Yamashita; Toru Aizawa (Endocrine Journal)
Elevated Fulminant Index (FI), [plasma glucose (PG)/glycosylated hemoglobin A1c (HbA1c)], was reportedly a sensitive index to differentiate fulminant type 1 diabetes (FT1D) from non-fulminant T1D (nFT1D). Aim of this study was to describe a better, but simpler index of FT1D. 49 and 52 patients with FT1D and nFT1D, respectively, were registered, and the discriminating ability of the rounded, normalized ratio, [PG (mmol/L) – 5.0]/[HbA1c (%) – 5.0], and the original ratio, [PG (mmol/L)]/[HbA1c (%)], was compared. Normalizing the ratio significantly raised its accuracy: area under the curve for receiver operating curve, AUROC (95%CI), 0.927 (0.858–0.964) and 0.851 (0.763–0.910), respectively, with and without the normalization (p < 0.01). Rounding of the figure into [PG (mmol/L) – 5.0]/[HbA1c (%) – 5.0] did not significantly sacrifice the discriminating ability of the index. Namely, the optimal cut point of rounded and normalized GAR, 10.0, showed 89.8% sensitivity. In conclusion, rounded, normalized (rn) GAR ≥10 (the rounded optimal cut-off) could be used for the snap diagnosis of FT1D.